Finding sensory profilers amongst red wine composition: a novel nationwide approach - José-Simões Coutinho, A. (2017)
The objective of this work was to verify the signaling/profiling potential of wine compounds and the physicochemical and bioclimatic winerelated measurements on a nationwide sensory scale of red wine typicality. Color tonality evolved from violet-purple in cooler northern regions to ruby-garnet in hotter southern regions. Acidity and astringency were enhanced from south to north. Conversely, alcohol and viscosity progressed southward. Bitterness was primarily affected by inland-coastal influence. The regional differentiation of astringency and bitterness introduced an orthogonal reading (N north- S south vs. E inland-W coastal, respectively), rather than a linear one, these findings adding novelty to sensory research. Additionally, several Portuguese-related studies were reviewed, and their findings were correlated with six sensory measures. Bioclimatic indexes, pH and the total phenol index were considered the strongest profilers in a nationwide assessment on red wine typicality. The ratio of the oligomeric/polymeric composition of tannins, as well as total anthocyanins, was also to be considered to be a valid sensory profiler. Several nationwide tendencies and correlations between sensory evaluations and wine chemistry may represent interesting findings and challenge unexplored ways for new research.